Association of prostate-specific antigen and prostate volume in benign prostatic hyperplasia patients with urinary tract infection - Feren Altagracia Da Leo; Tejo Jayadi; Jonathan Willy Siagian (Surgical Residency Program Syiah Kuala University, 2022)
Introduction: One of the most common diseases in men is benign prostatic hyperplasia (BPH). In this condition, the prostate gland becomes larger, thus it can clamp the urinary tract area and cause obstruction. Obstruction in the lower urinary tract increases the high risk of urinary tract infections (UTI). When the prostate volume becomes larger, the levels of prostate-specific antigen increase. This research aims to determine the correlation between PSA levels and prostate volume in BPH patients with urinary tract infections (UTI). Methods: This study used an analytic observational method with a cross-sectional design. Data were taken from the medical records of BPH patients suffering from UTIs at Bethesda Hospital Yogyakarta from January 2018 to December 2020. Data collection was carried out from January 17 2022 to March 17 2022. The data used in this study were selected using inclusion and exclusion criteria so that the obtained 33 medical record data were analyzed. The data used in this study were analyzed using SPSS software. The univariate analysis describes the distribution of data. Bivariate analysis used the chi-square test so that it could show the relationship between the independent variable (prostate volume) and the dependent variable (PSA level). Result: The data show moderate prostate volume (30-80cc) in 17 (51.5%), high prostate volume (>80ml) in as many as 9 patients (27.3%) and normal prostate volume (<30 ml) in as many as 7 patients (21.2%). High PSA levels are 26 (78.8%) and normal PSA levels are 7 patients (21.2%) that noted. Bivariate analysis data with a chi-square test shows that the significant score is 0.019 (p<0.05). Conclusion: The research shows an association of PSA levels and prostate volume in BPH patients with UTI.